EP290/#660 First report of clinical outcomes with escalated doses of cisplatin and doxorubicin in PIPAC for peritoneal carcinomatosis of epithelial ovarian cancer. (4th December 2022) - Somashekhar, Sp; Kumar, Rohit; Kapoor, Priya; Rakshit, Susmita; Fernandes, Aaron; Karthik, HK; Rajagopal, Ashwin
Abstract : Objectives: PIPAC in inoperable recurrent ovarian cancer has showed better oncological outcomes at existing doses. However the maximum dose that can be used and its clinical outcomes is not defined yet. Methods: PIPAC was done at dose of cisplatin 15 mg/m2 and doxorubicin 3 mg/m2. The patient demographics, perioperative findings, adverse events, and outcomes were prospectively recorded. Response rate was graded as Peritoneal Regression Grading Score (PRGS). QoL of the patients was studied according to the EORTC QLQ – C30 score. Results: 18 PIPAC administrations were performed in 6 patients. The median hospital stay was 1.5 day (1–3 day). CTCAE grade 2 was observed in 3 patients, for abdominal pain and nausea, grade 3 fatigue in 2 patients. Transient increase in C- reactive protein was seen in 3 patients, haematological, renal and hepatic functions were not impaired in any patients except for mild transient elevation in AST and ALT levels in 3 patients. All patients completed 3 cycles of PIPAC. Of the 6 patients, 3 had complete response (PRGS 1) and remaining 2 had major (PRGS 2), 1 had minor response (PRGS 3). There was improvement in functional scale, symptom scale and overall global health status for all patients. Conclusions: PIPAC can be performed safely at doses of cisplatin 15 mg/m2 and doxorubicin 3 mg/m2. There is better objective & pathological response with this dose with no major complications or side effects to the patients. There is also improvement in quality of life. This dose should be new standard of care for further studies.